Re-inventing PTPTN study loan with blockchain and smart contracts - Gazali, Haneffa Muchlis; Hassan, Rusni; Mohd Nor, Rizal; Rahman, Hafizur M.M (IEEE, 2017)
The issue of default payments from borrowers of the National Higher Education Fund Corporation (PTPTN) is worrisome. Many borrowers fail to pay their loans and claims that the PTPTN has poor management and filing system. This study proposed a prototype for managing study loan repayment utilizing blockchain and smart contracts. Borrowers have full access toward their accounts and ledgers while corporation filing and management system get automatically up-to-date with the assistance of smart contracts.